2018
DOI: 10.1200/jco.2016.71.3495
|View full text |Cite
|
Sign up to set email alerts
|

Enzalutamide for the Treatment of Androgen Receptor–Expressing Triple-Negative Breast Cancer

Abstract: Purpose Studies suggest that a subset of patients with triple-negative breast cancer (TNBC) have tumors that express the androgen receptor (AR) and may benefit from an AR inhibitor. This phase II study evaluated the antitumor activity and safety of enzalutamide in patients with locally advanced or metastatic AR-positive TNBC. Patients and Methods Tumors were tested for AR with an immunohistochemistry assay optimized for breast cancer; nuclear AR staining > 0% was considered positive. Patients received enzaluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
308
2
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 389 publications
(332 citation statements)
references
References 33 publications
10
308
2
12
Order By: Relevance
“…The AR is the focus of therapeutic targets in adjuvant and neoadjuvant setting in recent and ongoing clinical trials. 23, 24 AR is not among the genes included in PAM50 and we did not have access to tissue blocks to perform immunohistochemistry for AR to test if the increase in HER2-encriched subtype in older patients correlates with LAR subtype.…”
Section: Discussionmentioning
confidence: 99%
“…The AR is the focus of therapeutic targets in adjuvant and neoadjuvant setting in recent and ongoing clinical trials. 23, 24 AR is not among the genes included in PAM50 and we did not have access to tissue blocks to perform immunohistochemistry for AR to test if the increase in HER2-encriched subtype in older patients correlates with LAR subtype.…”
Section: Discussionmentioning
confidence: 99%
“…A series of clinical trials which test the efficacy of marketed AR antagonists such as bicalutamide and enzalutamide to treat AR + TNBC have been started (eg, NCT02353988, NCT00468715, and NCT01889238) . For locally advanced or metastatic AR + TNBC, the treatment by enzalutamide showed 25% clinical benefit rate at 16 weeks, 2.9 months of median progression‐free survival, and 12.7 months of median overall survival, demonstrating the clinical activity of AR antagonists in the difficult‐to‐treat BrCa …”
Section: Ar and Other Cancersmentioning
confidence: 96%
“…Despite the reported association of AR with a better outcome in this disease context, there has been much enthusiasm for therapeutic targeting of AR, particularly in TNBC, as there are currently no targeted therapies for the treatment of this aggressive disease subtype. The mainstream clinical approach has been AR antagonism based on in vitro and in vivo preclinical studies, suggesting that AR has oncogenic activity in some ERa-negative breast cancer models (18)(19)(20)(21)(22)(23)(24)57), and two clinical trials of women with advanced TNBC have reported efficacy with this approach (58,59). However, in vitro studies have demonstrated dichotomous proliferative effects of androgens in different AR-positive ERa-negative breast cancer cell lines (15,(20)(21)(22), other AR-positive ERa-negative breast cancer cell lines (MFM-223 and CAL-148) are inhibited (25,60).…”
Section: Discussionmentioning
confidence: 99%